2023
DOI: 10.1039/d2nr05847b
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic improvement in the stability and mechanism of high-performance inverted polymer solar cells featuring a solution-processed buffer layer

Abstract: In this paper we demonstrate inverted PTB7:PC71BM polymer solar cells (PSCs) featuring a solution-processed s-MoO3 hole transport layer (HTL) that can, after thermal aging at 85 °C, retain their initial...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…62 Although this phenomenon is controversial because the exact causes remain unclear, 63 we can attribute this to the interfacial instability between the BHJ and MoO x layers. 64 When we exclude the initial 200 h (burn-in loss), we can confirm the excellent thermal stability of the PID -processed OSC, which retained 98% of its initial PCE after 1000 h, in contrast to the pristine and CN-processed OSCs. This difference was likely owing to the solid additive, which can maintain BHJ morphology under continuous thermal stress, as confirmed by the TRPL results.…”
Section: Resultsmentioning
confidence: 64%
“…62 Although this phenomenon is controversial because the exact causes remain unclear, 63 we can attribute this to the interfacial instability between the BHJ and MoO x layers. 64 When we exclude the initial 200 h (burn-in loss), we can confirm the excellent thermal stability of the PID -processed OSC, which retained 98% of its initial PCE after 1000 h, in contrast to the pristine and CN-processed OSCs. This difference was likely owing to the solid additive, which can maintain BHJ morphology under continuous thermal stress, as confirmed by the TRPL results.…”
Section: Resultsmentioning
confidence: 64%
“…For the preparation of the S-MoO 3 solution, 0.1 g of molybdenum powder was dispersed in 10 mL of ethanol in an ultrasonication bath for 30 min. Subsequently, 0.35 mL of 30 wt% hydrogen peroxide was added to the solution to obtain hydrogen transition metal as the dried powder of S-MoO 3 [22]. The dried powder was then dissolved in 10 mL of ethanol and stirred for 1 day.…”
Section: Methodsmentioning
confidence: 99%
“…Alongside that, Sung et al demonstrated the use of a solution-processed S-MoO 3 HTL in inverted PTB7:PC 71 BM polymer solar cells, obtaining high PCE and excellent stability. Under damp-heat conditions of 65 • C/65% relative humidity (R.H.), the T 80 value measured was 1350 h, and the T 90 value for 85 • C/air was 4400 h. The S-MoO 3 HTL also displayed excellent photo-stability under continuous illumination with AM 1.5G light [22]. Moving beyond MoO x -based materials, Ioakeimidis et al introduced a solution-processed antimony-doped tin oxide (ATO) hole-selective contact produced by a spray pyrolysis route [23].…”
Section: Introductionmentioning
confidence: 99%
“…In these cells, we used PDINO as the ETL material, reported as a promising interlayer that provides a highly photostable inverted nonfullerene organic solar cell. 12 We selected MoO 3 as the HTL based on the reported information in the literature [21][22][23][24][25] and in our previously reported work, 19 where better stability of the iOSCs is observed, in comparison with other materials used as HTLs.…”
Section: Introductionmentioning
confidence: 99%
“…We selected MoO 3 as the HTL based on the reported information in the literature 21–25 and in our previously reported work, 19 where better stability of the iOSCs is observed, in comparison with other materials used as HTLs.…”
Section: Introductionmentioning
confidence: 99%